Warning Model of the Ionic Rare Earth Mine Slope Based on Creep Deformation Time Series. (8th December 2021) - Wang, Dan; Rao, Yun-zhang; Han, Min; Shi, Liang; Liu, Li; Zhang, Mei-dao
Abstract : This paper takes the actual working conditions of leaching mining, with the Xikeng Rare Earth Mine in Anyuan County as the research object. The slope surface monitoring as a technical means is used to analyze the deformation characteristics, including cumulative displacement, velocity, and acceleration, and the leaching slope and establish an early warning system to assist with leaching production. The study shows that there are three stages in the process of ionic rare earth mine slope deformation, i.e., the initial stage with deformation velocity in 0.15 to 0.30 mm∙h -1, the speed of the uniform deformation stage fluctuating but maintaining at -0.15 to 0.15 mm∙h -1, and the accelerated deformation stage when the velocity and acceleration are 3 to 10 times or more than those of the initial deformation stage. The practice had proved that the monitoring system responded positively when an alarm based on the Local Outlier Factor (LOF) was issued so that the production process was in a safe state and no large-scale landslide disaster occurred. This study will provide theoretical and technical support for the safe and efficient mining of rare earth in situ leaching.